PSYCHOSOCIAL IMPACTS OF UNTREATABLE DISEASE ON PATIENTS AND THEIR MATRIMONIAL RELATIONSHIP - Ihsan Ullah; Prof. Dr. Arab Naz (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
This study was conducted to explore and interpret the impacts of incurable illness on patients and social relationships of partners in Khyber Pakhtunkhwa province of Pakistan. Forty (40) terminally ill patients were selected purposively and interviewed individually (26 male & 14 female patients) by the way of open-ended questions. Several themes were extracted following verbatim transcripts. All the participants clarified the impacts of untreatable illness on their social lives and the positive and negative aspects of their matrimonial relationship. Anger, depression, and desperation were noticeable in the terminal patients. Likewise persistent sadness, bitterness, guilt and loss were common in the patients and alternatively in their partners as explained by the respondents. This research underlines a distinct viewpoint on the damaging influences which terminal illness can have on the marital relationship. However it also recommends how to deal the situation in a positive manner by making adjustments required by the concerned illness. The findings indicate that social scientists need to confess and reply to the incredible psycho-social impacts that serious illnesses and related medical procedures can have on the patients and their families even in this modern age of advance technology. Advance social and psychotherapeutic techniques and socio- psychological support of partners can assist such patients to maintain a balanced spousal relationship and live with a positive life style till death.